Phylogenetic relationship of local rice from Central Java, Indonesia with Pokkali variety based on Single Nucleotide Polymorphism (SNP) markers - QORI NUR FAUZIAH; EDI PURWANTO; MUJI RAHAYU (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fauziah QN, Purwanto E, Rahayu M. 2024. Phylogenetic relationship of local rice from Central Java, Indonesia with Pokkali variety based on Single Nucleotide Polymorphism (SNP) markers. Biodiversitas 25: 3965-3973. Rice (Oryza sativa L.) is a major food crop in Asia particularly susceptible to the effects of climate change, with drought being a significant threat to productivity, potentially reducing yields by up to 50%. Indonesia is the largest producer of rice in Asia, with Central Java contributing up to 18% of the total, but the production of high-yielding varieties remains constrained. The objective of plant breeding is to ensure the sustainability of rice production by developing superior varieties. Therefore, this study aimed to develop local Central Java rice varieties tolerant to drought using the unique identification power of Single Nucleotide Polymorphism (SNP) markers. The potential impact of this research is the development of drought-tolerant rice varieties that could significantly improve rice production in Central Java. The experiment was conducted in Karanganyar and at the UGM campus, comprising several stages, including isolation, DNA amplification, and sequencing analysis. The results showed that based on sequencing analysis using BLAST, SNP was present in both the control and local rice varieties. The sequencing results were analysed for phylogenetic relationship using MEGA 11, showing thatPutih Mutiara (Klaten), Merah Sengreng (Boyolali), and Merah Wangi (Klaten) had the closest evolutionary relationship, and the most identical genetic structure to Pokkali varietycompared to the two controls (IR64 and Ciherang), and three local rice varieties namely Putih Mentikwangi (Karanganyar), Hitam Mutiara (Karanganyar), and Hitam Cempo (Boyolali).